Characterization and antioxidant activities of the polysaccharides from mycelium of Phellinus pini and culture medium. (6th March 2015) - Jiang, Peng; Yuan, Lei; Cai, Dongling; Jiao, Lili; Zhang, Liping
Highlights: Two heteropolysaccharides were isolated from mycelium and culture medium of Phellinus pini . PPM and PPE were heteropolysaccharides with various molecular properties. PPM possessed better antioxidant activity in vitro than PPE. PPM could be explored as novel antioxidants in functional foods and medicine. Abstract: Two polysaccharides isolated and purified from the mycelium (PPM) and its culture medium (PPE) of Phellinus pini using gel filtration were subjected to composition analysis and valuated for the antioxidant activity. The average molecular weights of PPM and PPE were approximately 22.0 and 38.0 kDa, respectively. PPM and PPE were both neutral heteropolysaccharides consisting of mannose, galactose, and glucose with molecular ratios of 2.99:1.00:0.34 and 38.40:1.00:1.76, respectively. In vitro antioxidant assay, PPM and PPE could scavenge 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical and hydroxyl radical, chelate ferrous ion and reduce ferric ion. The antioxidant activities of PPM were stronger than those of PPE, suggesting that PPM has significant potential as a natural antioxidant agent.